NVDI analysis in a transition area of cerrado and secondary vegetation in the municipality of Vigia-Pará-Brasil (Research, Society and Development, 2022)
This study aimed to analyze the changes in use and vegetation cover in the municipality of Vigia and to evaluate the Normalized Difference Vegetation Index-NDVI in a transition area of ​​cerrado and secondary vegetation in the same municipality. Presenting two different scales, one at the municipal level and the other analysis was at the local level. The Grassland class showed an increase, from 107 km² in 1985 to 108 km² in 2018, losing area to the Urban and Secondary Vegetation classes, 9.85 km² and 60.43 km², respectively. The Secondary Vegetation Class showed an increase of 32.92 km², from 161.13 km² in 1985 to 194.05 km² in 2018, with the main contribution of the pasture class with 60.43 km². The Cerrado class showed a significant decrease, in 1985 the municipality of Vigia had 9.85 km², decreasing to 4042 km² in 2018, loss of 5.42 km² of Cerrado area, losing to urban classes, pasture and secondary vegetation. Concluding that the monitoring of land use and land cover becomes important for areas considered to be non-forest like the Cerrado, especially in the Amazon biome, due to the peculiar characteristics of transition between Cerrado and other types of vegetation, because with monitoring it is possible detect degradation and deforestation, thus contributing to the management of public policies aimed at preserving the biodiversity of these areas.